Assessment of Visual and Auditory Feedback on the Quality of Chest Compressions in Pediatric Basic Life Support Trainings - Ayça Aydoğan; Oğuz Dursun (Galenos Yayinevi, 2018)
Introduction: The primary objective of the study was to assess the effects of training including visual and auditory feedback on the adequacy of resuscitation procedures. Methods: The study was conducted with 31 research associates of the department of pediatrics at the simulation center in Akdeniz University Faculty of Medicine. The depth and the number of chest compression were recorded by receptors placed on the model during the two-minute resuscitation. One week after the initial assessment, 5-minute hands-on training including individual visual and auditory feedback was provided. Afterward, the efficacy of the training in reaching the desired goals was investigated by repeating the initial assessment. Results: In the study, a statistically insignificant increase from 4.44±0.9 to 4.67±0.9 could be obtained in the mean depth of compression after the training while the mean number of chest compression decreased from 123.8±20/min to 113.7±22/min after the training. The mean percentage of compression at the targeted rate increased from 27.9% to 53.6%. Conclusion: Individual training with visual and auditory feedback is effective in improving the quality of resuscitation. It has provided an increase in the compression rates at the targeted rate and depth. After the training, it was observed that the variability among the research associates in terms of the rate and depth of chest compressions still remained significant. In order to define the ideal training technique, there is a need for studies comparing the results of repetitive vocational training courses and training courses provided using different techniques.